Mean Platelet Volumes of Infants With Acute Bronchiolitis, is There a Correlation Between Them? - Burçin NALBANTOĞLU; Nuriye Ece MİNTAŞ; Ayşin NALBANTOĞLU; Mustafa Metin DONMA; Nedim SAMANCI (Namık Kemal Tıp Dergisi, 2018)

(untitled)
Aim:Acute bronchiolitis is the most common lower respiratory tract infection of children younger than 2 years of age. There aren't any standardized diagnostic criteria and severity assessment classifications for acute bronchiolitis available in literature. Mean platelet volume (MPV) has shown to be effected in inflammatory conditions and to our knowledge there's only one recent study in children with acute bronchiolitis that demonstrated an association between MPV change and acute brınchiolitis.Materials and Methods:In this retrospective study we enrolled 555 children diagnosed with Acute bronchiolitis and 516 healthy infants with a matching age and sex.Results:MPV levels were found significantly higher in patient group (8,2 ± 0,8 fL) than the control group (7,9 ± 0,8 fL). In terms of hospitalization need, no significant difference was detected between the MPV values of the hospitalized group and the outpatients (8,3±0,8 fL; 8,2±0.7 fL, respectively).Conclusions:In conclusion, our data show that MPV values are significantly elevated in acute bronchiolitis compared to healthy infants. However, MPV can't be used as a guidance in attack severity nor can it predict hospitalization and systemic steroid need.